SIKAP, KEPUASAN, DAN POLA PEMBELIAN KONSUMEN CAKE BANANA FOSTER DI KOTA BANDAR LAMPUNG - Wahyu Dewangga; Wuryaningsih Dwi Sayekti; Rabiatul Adawiyah (Lampung University, 2023)
This study aims to analyze the attitude, satisfaction and consumer purchase patterns of Banana Foster cake in Bandar Lampung City. This research was conducted at outlets of Lampung Banana Foster in Bandar Lampung City. The research method is a survey with accidental sampling technique. Respondents were 58 Banana Foster cake consumers who had bought and consumed Banana Foster cake at least once in the last three month. The research data are analyzed using Fishbein Multi-attribute analysis, Customers satisfaction Index (CSI) and descriptive statistics analysis. The attributes used in this study are taste, price, flavor variants, texture, scent, cleanliness, halal’s label and expired date. Data collection was conducted in November - December 2021. The results showed that the consumers liked Banana Foster cake or had a good attitude with an Ao value was 123.12. Consumers bought cake at Banana Foster mostly because of the taste. Customer Satisfaction Index (CSI) in consuming Banana Foster cake was in the satisfied criteria (77.17 %). The highest amount of Banana Foster’s cake purchased was black premium flavor, the average number purchased was 1.24 pieces per household per three months, and the average frequency of consumer purchase was two times for three month. Key words: cakes, consumer attitude, customer satisfaction, purchasing patterns